Time Use and Educational Attainment: A Study of Undergraduate Students - Etcheverry, Emily J.; Clifton, Rodney A.; Roberts, Lance W. (Canadian Journal of Higher Education/La Revue canadienne d’enseignement supérieur, 1993)
This research examines the effects of students’ time use in academically related activities and paid employment on their educational attainment. A theoretical model containing fourteen background, social psychological, time use, and educational attainment variables was formulated. The data were obtained from questionnaires administered to 308 undergraduate students in the Faculty of Education at a Western Canadian University. A stratified random cluster sampling procedure was used to select classes of students. Structural equation modelling is used to test the relationships among the variables. Results indicate that when other variables are taken into account, the time students spend in academically related activities and paid employment has little effect on their educational achievement and their educational expectations.